1976
DOI: 10.1246/bcsj.49.3493
|View full text |Cite
|
Sign up to set email alerts
|

Complexes between Nucleotide Base and Amino Acid. II. Crystal Structure of 5-Bromocytosine : N-Tosyl-l-glutamic Acid

Abstract: The complex crystals of 5-bromocytosine and N-tosyl-l-glutamic acid were obtained from their aqueous solution. The space group is P1 with dimensions of a=10.843(1), b=11.690(2), c=10.879(2) Å, α=122.15(1), β=121.38(1), γ=69.93(1)°, and Z=2. The structure was solved by the heavy atom method and refined by a block-diagonal least-squares method. The undissociated γ-carboxyl group of glutamic acid is bound with O(2) and N(4) of 5-bromocytosine through hydrogen bonds. This interaction mode is different from those f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…. O 2 (cytosine) (1215,1216). Undissociated carboxyl groups are also observed in thymidine 5'-carboxylic acid where thymine 0 4 and N3-H groups are hydrogen bonded with the carboxyl moiety (1217), and in a nucleoside dipeptide with the terminal carboxyl interacting with adenine NJf and N7 (1218).…”
Section: Model Systems Involving Nucleic Acid and Protein Constituentsmentioning
confidence: 99%
“…. O 2 (cytosine) (1215,1216). Undissociated carboxyl groups are also observed in thymidine 5'-carboxylic acid where thymine 0 4 and N3-H groups are hydrogen bonded with the carboxyl moiety (1217), and in a nucleoside dipeptide with the terminal carboxyl interacting with adenine NJf and N7 (1218).…”
Section: Model Systems Involving Nucleic Acid and Protein Constituentsmentioning
confidence: 99%
“…Nevertheless, its crystal structure has not been reported to date. The co-crystal of (I) and 5-bromocytosine has been characterized (Ohki et al, 1976). Our previous studies showed that (I) crystallizes as and polymorphs.…”
Section: Commentmentioning
confidence: 99%
“…Cytosine (C) base has been the subject of several investigations aiming to study the relative stabilities of tautomeric forms (Kobayashi, 1998), hydration effects and hydrogen bonding (Sivanesan et al, 2000). The structures of nucleotide complexes, especially cytosine along with amino acids, were extensively studied (Ohki et al, 1974(Ohki et al, , 1975(Ohki et al, , 1976Takenaka et al, 1980). As we have been interested in hydrogen bonding patterns involving aminopyrimidine±carboxylate interactions, we have recently determined the crystal structures of cytosinium hydrogen maleate (Balasubramanian et al, 1996), trimethoprim salicylate monohydrate (Murugesan & Muthiah, 1996), trimethoprim formate (Umadevi & Muthiah, 1994) and trimethoprim maleate (Prabakaran et al, 2001).…”
Section: Commentmentioning
confidence: 99%